Analisis Komparatif Kitab Tarjuman Al-Mustafid dengan Tafsir Anwar At-Tanzil dan Tafsir Jalalain pada Ayat-ayat Sihir - Anwar, Muhammad Khoirul; Rofidah, Izzah; Jannah, Zahrah Raudhatul (Al-Irfani: Journal of Al Qur'anic and Tafsir, 2024)
This research presents a comparative analysis between the Tarjuman Al-Mustafid book with Anwar At-Tanzil's commentary, and Jalalain's commentary with a focus only on magic verses starting from Surah Al-Fatihah, Al-Baqarah verse 102, and Al-Falaq. The research method used is a qualitative approach focused on library research with the main data coming from the books of Tarjuman Al-Mustafid, Tafsir Anwar At-Tanzil, and Tafsir Jalalain. The results of the research show that there is quite a big influence from Anwar At-Tanzil's interpretation and Jalalain's interpretation on Tarjuman Al-Mustafid in terms of the systematic writing and meaning of the verses. One important factor in the relationship with the interpretation of Jalalain is Abdurrauf's intellectual connection with Jalaluddin As-Suyuti, the author of the interpretation of Jalalain. Apart from that, Anwar At-Tanzil's tafsir is also an important reference source in writing this tafsir, as stated on the cover of Tarjuman Al-Mustafid's tafsir. In understanding the magic verses, Abdurrauf is more inclined or agrees with Tafsir Jalalain because it is used as a reference, and is influential when providing a more general explanation.